(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article delves into the psychological intricacies of desire as depicted through the characters in "Almost the Heaven" by Judith McNaught and "Bygone Days" by Abdulla Kadiri. Through an examination of the lexical choices employed by the characters, this study aims to uncover the underlying emotions, conflicts, and motivations driving their desires. Utilizing the IMRAD structure, the article provides a comprehensive analysis of how different lexical units contribute to the portrayal of desire and psychological depth within the novels.